12-19 = -7x

In this equation, x is the variable so we must solve for x:

First simplify:

-7 = -7x

Now to get x (the variable) by itself, we need to divide both sides by -7:

`-7/-7 = (-7x)/-7`

`therefore1=x`

`therefore` **x=1**

To check that this satisfies the equation, substitute x=1 into

12-19= -7x

`therefore` -7=-7 (1)

`therefore -7=-7`

**Therefore x=1 satisfies the equation**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.